2017
DOI: 10.3390/cryst7050126
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Dielectric Properties of PTFE-Based Composites Filled by Micron/Submicron-Blended CCTO

Abstract: This paper investigated a polymer-based composite by homogeneously embedding calcium copper titanate (CaCu 3 Ti 4 O 12 ; CCTO) fillers into a polytetrafluoroethylene matrix. We observed the composite filled by CCTO powder at different sizes. The particle size effects of the CCTO filling, including single-size particle filling and co-blending filling, on the microstructure and dielectric properties of the composite were discussed. The dielectric performance of the composite was investigated within the frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The laminates are PTFEbased materials produced by [49,50] Further analysis showed that the ε and ε of PTFE/recycled BRS composites increased with the reduction in recycled BRS filler size (Table 2), in agreement with previous work [12,36]. This behaviour is attributed to the higher densification and stronger interfacial polarisation [3]. Composites reinforced with smaller grain-sized particles tend to possess a more significant interfacial area, leading to extra interfacial polarisation, which increases the dielectric properties [12,48].…”
Section: Signal Transmission Speedsupporting
confidence: 84%
See 2 more Smart Citations
“…The laminates are PTFEbased materials produced by [49,50] Further analysis showed that the ε and ε of PTFE/recycled BRS composites increased with the reduction in recycled BRS filler size (Table 2), in agreement with previous work [12,36]. This behaviour is attributed to the higher densification and stronger interfacial polarisation [3]. Composites reinforced with smaller grain-sized particles tend to possess a more significant interfacial area, leading to extra interfacial polarisation, which increases the dielectric properties [12,48].…”
Section: Signal Transmission Speedsupporting
confidence: 84%
“…The effect of recycled BRS filler size on the density of the PTFE matrix is shown in Figure 6. The 106 μm, 90 μm, 63 μm, 45 μm, 25 μm, recycled BRS composites had density values of 2.17, 2.18, 2.19, 2.20, and 2.21 g/cm 3 , respectively. Thus, decreasing recycled BRS particle size led to the increase in the density of the composites.…”
Section: Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…73 The effect of filler addition in enhancement of dielectric permittivity of different polymers can be perceived from Table 5. In general, pristine PI is used as a polymer matrix because it has good mechanical properties, in addition to high chemical and thermal stability, but the dielectric constant ε ≈ 3.5, 74,75 and the dielectric permittivity has been several times enhanced (28.42 times, 72 26.6 times, 75 4 times, 76 Low dielectric constants materials are also equally important in the field of modern IC to minimize both cross-talk noise and resistance capacitance delay. 81 Recently, various methods have been introduced to develop PIs with low and ultra-low dielectric constant materials, 82 in particular, well-designed organic-inorganic hybrid materials systems have been gaining attraction significantly for microelectronics because of their utilization in ICs 83 and also systems with pore voids or air gap were used.…”
Section: Role and Effect Of Filler/hybrid Filler Addition On Dielecmentioning
confidence: 99%
“…insulating and exible behaviors of polymers [8] . Xie [9] et al introduced micron-sized calcium copper titanate (CCTO) into polytetra uoroethylene (PTFE) and fabricated the CCTO/PTFE composites by emulsion polymerization and subsequent hot-pression method. The dielectric constant of 30 vol% CCTO/PTFE composite increased to 25.6, 3 times higher than that of pure PTFE.…”
Section: Introductionmentioning
confidence: 99%